GluA2 is rapidly edited at the Q/R site during neural differentiation in vitro - Pachernegg, Svenja; Münster, Yvonne; Muth-Köhne, Elke; Fuhrmann, Gloria; Hollmann, Michael (Frontiers in Cellular Neuroscience, 2015)
The majority of AMPA receptors in the adult brain contain GluA2 subunits, which can be edited at the Q/R site, changing a glutamine to an arginine within the ion pore. Q/R editing renders AMPARs virtually Ca2+-impermeable, which is important for normal AMPA receptor function. Thus, all GluA2 subunits are Q/R-edited in the adult brain. However, it has remained controversial precisely when editing sets in during development. In the present study, we show that GluA2 mRNA is very rapidly Q/R-edited immediately after its appearance, which is after 4.5 days of differentiation from 46C embryonic stem cells (ESCs) to neuroepithelial precursor cells (NEPs). At this time point, most of the GluA2 transcripts were already edited, with only a small fraction remaining unedited, and half a day later all GluA2 transcripts were edited. This can be explained by the observation that the enzyme that Q/R-edits GluA2 transcripts, ADAR2, is already expressed in the cell well before GluA2 transcription starts, and later is not significantly upregulated any more. Editing at another site works differently: The R/G site within the ligand-binding domain was never completely edited at any of the developmental stages tested, and the enzyme that performs this editing, ADAR1, was significantly upregulated during neural differentiation. This confirms previous data suggesting that R/G editing, in contrast to Q/R editing, progresses gradually during development.